Pooled analysis of three pharmacokinetic studies comparing biosimilar MB02 and reference bevacizumab - B. Miguel‐Lillo; Sara Sánchez‐Vidaurre; L. Pérez Díaz; A. Paravisini (Wiley, 2023)
Abstract Aim The aim of this study was to add robustness and provide further evidence on the bioequivalence, safety and immunogenicity between MB02 and reference bevacizumab. No similar study has been performed before with a biosimilar monoclonal antibody. Methods Population analysis by pooling data from three independent pharmacokinetic (PK) studies was performed. The studies had a single‐dose, double‐blind, three‐arm, parallel‐group design and two studies, MB02‐A‐02‐17 and MB02‐A‐05‐18, compared MB02 to EU‐ and US‐bevacizumab in Caucasian subjects, while study MB02‐A‐04‐18 compared MB02 and EU‐bevacizumab in Japanese participants. Primary endpoints included maximum observed serum concentration (Cmax), area under the serum concentration-time curve (AUC) from time zero and extrapolated to infinity (AUC0-∞) and AUC from time zero to the time of last quantifiable concentration (AUC0-t). Secondary endpoints included other PK parameters, safety and immunogenicity. A sensitivity analysis using actual protein concentration as a correction factor was applied to primary PK parameters. Results Point estimates and 90% confidence intervals for the geometric mean ratios of primary PK parameters for MB02, EU‐ and US‐bevacizumab were all contained within the predefined bioequivalence margins (80%-125%) for all pairwise comparisons. The same results for all pairwise comparisons were observed when protein‐corrected primary PK parameters were analyzed. Safety and immunogenicity were similar between MB02 and the EU‐ and US‐reference bevacizumab in healthy subjects. Conclusions This pooled analysis of three comparable PK studies further supports the bioequivalence of biosimilar MB02 to EU‐ and US‐reference bevacizumab. No clinically meaningful differences in safety or immunogenicity were observed.